Special exponential functions on lattices of simple Lie groups and allotropic modifications of carbon - Nesterenko, M. O. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9 Modern definitions and properties of special orbits-functions of simple Lie algebras are systematized. Models of carbon modifications related to simple Lie algebras and Coxeter groups are proposed.